Development of Selected Marketing and Economic Indicators Within the Growing of Oilseed Rape in the Slovak Republic - Dušan Dobák; Katarína Klimentová; Roman Récky (Polityki Europejskie, Finanse i Marketing)
Growing of oil crops has spread considerably in the last years. The most important oil crop grown in our conditions is oilseed rape. In this paper we evaluate the growing of oilseed rape from the production and economic point of view. We focused on the years 2004 – 2010. Obtained results show that the economic advantage of oilseed rape growing is affected mainly by the climatic conditions as well as by the intensification of production and support policy. The year 2008 was economically most advantageous of evaluated years. The highest loss within the growing of oilseed rape was recorded in 2009. Higher hectare yield of oilseed rape can be achieved by the intensification of production.